A Comparison of Ankle Joint Position Sense in Female Students with and without Pronated and Supinated Foot - Saide Nobakht; Foad Seidi; Reza Rajabi (Sport Sciences and Health Research)
Since musculoskeletal disorders may impair proprioceptive function, the aim of this study was to compare the ankle joint position sense (AJPS) in female students with and without pronated and supinated foot. So, 87 Subjects were divided into three groups (pronated, supinated and normal foot, each group 29 subjects). The accuracy of the AJPS was assessed by absolute error of reconstruction of angles of 10° dorsiflexion and 20° plantar flexion using an electrogoniometer. The Kruskal-Wallis test results revealed no significant differences in the mean absolute error of reconstruction of angles of 10° dorsiflexion and 20° plantar flexion of the ankle among the groups (P=0.38, P=0.58). Based on the results of the study, on the one hand, it seems that the pronated and supinated abnormalities do not play a decisive role in the accuracy of proprioceptive function of the ankle joint and there are only structural and biomechanical changes. On the other hand, if the study is carried out in subjects with more severe abnormalities and a method in closed kinetic chain (but without engaging the adjacent joints) is used for angle reconstruction of ankle joint, different results may be achieved.